Gerakan Dakwah Pada Organisasi Perti: Historis, Pemikiran, Dan Implementasi Manajemen Dakwah Dalam Konteks Nasional Dan Global - Wahidin .; Suparto . (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This paper examines the da’wah movement within Persatuan Tarbiyah Islamiyah (PERTI), one of Indonesia’s oldest Islamic organizations, focusing on its historical foundation, religious thought, and organizational management in the context of national and global challenges. Founded in 1928 in Candung, West Sumatra, PERTI emerged as a traditionalist response to Islamic reform movements, maintaining Ahlussunnah wal Jamaah teachings through education and community-based da’wah. Using a qualitative descriptive approach with library research methods, this study explores the historical evolution of PERTI, its da’wah ideology, and its implementation of da’wah management. The findings show that PERTI emphasizes education as a central medium of da’wah, with madrasahs and pesantren functioning as centers of Islamic propagation and moral formation. The organization applies a collegial and consultative management model, integrating religious leadership and community engagement. However, PERTI faces modern challenges, including digital transformation, leadership regeneration, and competition with transnational Islamic movements. Strengthening digital literacy, enhancing educational modernization, and promoting inter-organizational collaboration are essential for PERTI’s continued relevance